Keris Palembang (Sebuah Kajian Fisual Terhadap Keris Palembang) - Basuki Teguh Yuwono (Ornamen, 2012)
Keris culture along Sumatera island known as the Malay keris, and the one that stands out is the dagger in Palembang culture. Although culture is not a culture dagger indigenous people of Palembang, but its existence is important and penetrated almost every joint of their lives. Palembang keris culture in the beginning of a culture that comes from the Javanese keris and keris culture influenced Bugis (South Sulawesi) and also under the influence of a keris culture of Minangkabau (West Sumatra). Span of the history and culture of the keris in Palembang supported community's ability to adjust and process keris culture coming from the outside gradually gave birth to the distinctive culture of dagger and reflect the characteristics of their culture and identity. The most striking feature can be seen from such a visualization of shape or keris. Palembang keris visualization can be identified through the shape of each piece keris, namely: 1) Blade / dagger eyes covering prestige, size, type, and others. 2) sampir / dagger sheath that covers various forms sampir and pendok. 3) Ulu / upstream dagger which includes various forms pangulu and pedongkok or mendak. Each part of the keris is visually has a unique appearance and characteristics. Keywords: Cultural Palembang keris, Javanese and Bugis influence,Â visual characteristics, eye dagger, slung, ulu.